Documenting new and little known leaf-mining Nepticulidae from middle and southwestern areas of the Asian continent - Stonis, Jonas R.; Remeikis, Andrius; Diškus, Arūnas; Navickaitė, Asta (Zootaxa, 2020)
We review eighteen species of Nepticulidae (Lepidoptera: Nepticuloidea) from Asia and describe eleven new species from Central Asia and the western Himalaya: Stigmella ziziphifolia Rocienė & Stonis, sp. nov., S. damocles Remeikis, sp. nov., S. pyramidata Diškus & Navickaitė, sp. nov., S. alilediella Diškus & Navickaitė, sp. nov., S. longa Remeikis & Stonis, sp. nov., S. latilobata Diškus & Navickaitė, sp. nov., S. paniculata Diškus & Navickaitė, sp. nov., Ectoedemia orbiculata Diškus, Remeikis & Stonis, sp. nov., Acalyptris brunipexus Stonis, Diškus & Remeikis, sp. nov., A. noctilucus Rocienė & Stonis, sp. nov., and A. nasutus Diškus & Navickaitė, sp. nov. The new taxa are illustrated with photographs of the adults, their genitalia, and, if available, leaf mines. We also provide the first photographic documentation of adults and male genitalia of some Asiatic species. We synonymize E. petrosa Puplesis with E. spinosella (de Joannis), and E. rosiphila Puplesis with E. ingloria Puplesis.